2017
DOI: 10.1111/boc.201600082
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Bordetella pertussis adenylate cyclase toxin affects integrin‐mediated adhesion and mechanics in alveolar epithelial cells

Abstract: These results suggest that mechanical and adhesion properties of the cells appear as pertinent markers of cytotoxicity of CyaA toxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 47 publications
(81 reference statements)
3
14
0
Order By: Relevance
“…287 It has already been shown that CyaA invasion results in a deep remodeling of the actinic 288 CSK localized essentially under the plasma membrane [9,44]. Present data obtained on cellular 289 adhesion as well as previous data obtained on early adhesion in the same cellular system [16] 290 show that CyaA significantly weakens the adhesion system, suggesting that 291 mechanotransduction signaling pathways are affected during the intoxication process.…”
Section: Discussion and Perspectives 275supporting
confidence: 58%
See 4 more Smart Citations
“…287 It has already been shown that CyaA invasion results in a deep remodeling of the actinic 288 CSK localized essentially under the plasma membrane [9,44]. Present data obtained on cellular 289 adhesion as well as previous data obtained on early adhesion in the same cellular system [16] 290 show that CyaA significantly weakens the adhesion system, suggesting that 291 mechanotransduction signaling pathways are affected during the intoxication process.…”
Section: Discussion and Perspectives 275supporting
confidence: 58%
“…Moreover, it has been shown that cAMP 343 modulates cell morphology by inhibiting a Rac-dependent signaling pathway [55]. Similarly, the 344 results obtained in our previous study on the early development of adhesion while the same cells 345 were intoxicated with the same toxin [16], have shown a reduction in chemical energy of 346 individual integrin-RGD ligand bonds as well as a diminution by two of integrin association at 347 the level of newly formed adhesion sites (clustering). For these two processes, the role of Rac 1 348 is fundamental [62] and its potential defect in parallel to the activation of RhoA could be the 349 common cause of these results.…”
mentioning
confidence: 66%
See 3 more Smart Citations